Level of mRNA Insulin Gene and Blood Glucose STZ-Induced Diabetic Rat are Improved by Glucomannan of Amorphophallus muelleri Blume from East Java Forest Indonesia - Fatchiyah, Fatchiyah; Nurmasari, Damai Aulia; Masruro, Nuri; Rohmah, Rista Nikmatu; Triprisila, Lidwina Faraline; Mulyati, Mulyati; Yamada, Takahisa; Ohta, Takashi (Journal of Tropical Life Science, 2019)
Diabetes mellitus is one of metabolic disorder with high level of blood sugar glucose and reduces pancreatic-insulin levels that are altered by unhealthy food and lifestyle. To manage the blood glucose and insulin level, we need the diabetes dietary management related with insulin gene cascade. The purpose of this study was to investigate the influence glucomannan fiber to mRNA level of the insulin gene and genes cascade expression of target cells of type 1 diabetic rat. Three-month-old male (Rattus norvegicus strain Wistar) were fed with fiber of glucomannan of Amorphophallus muelleri Blume with dosage 0,06g/kg BW and 0.12g/kg BW every day during one month. RNA dot blotting with specific cDNA probe was performed mRNA level of insulin gene. The result of this study showed that glucomannan could reduce of body weight and blood glucose level significantly. The mRNA level of insulin gene of diabetic rats-treated 0.12g/kg BW glucomannan fiber dosage was the highest significance level among of all groups. In histopathological analysis, glucomannan was increasing significantly in IRS-1 level expression proliferate properly and consistently increasing of the PI3-K expression level in treated diabetic rats. This study indicates that the 0.12g/kg BW glucomannan was optimum dosage that effectively as role for alternative high-fiber therapy of type 1 diabetic through insulin receptor tyrosine kinase pathway.Â